2007
DOI: 10.1208/aapsj0902023
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of S(−)-carvedilol in healthy volunteers after administration of the immediate-release (IR) and the new controlled-release (CR) dosage forms of the racemate

Abstract: Carvedilol is a b 1 -, b 2 -, and a 1 -adrenoreceptor blocker indicated for treatment of hypertension and mild-tosevere congestive heart failure. The objective of this study was to develop and evaluate a single population model that describes S ( -)-carvedilol pharmacokinetics from both the immediate-release (IR) and the new controlledrelease dosage forms of the racemate. Carvedilol IR data (1270 measurements) were obtained from 2 open-label studies (50 mg/25 mg Q12 hours for 2 doses). Carvedilol CR data (2058… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Consequently, the final model, a simple E max model with a fixed E 0 (-0.812%), was successfully used to describe rosuvastatin pharmacodynamics. Moreover, the robustness of the final model was evaluated by the nonparametric bootstrap and the datasplitting methods [51,52] , which indicated that selected combinations of data yielded results very similar to those obtained using the original full data set. The predictive performance of the final model was confirmed by the visual predictive check using Monte Carlo simulations, which showed that the mean values of LDL-C reduction (%) from the one-dose trials were mostly distributed within the 5th-to 95th-percentile boundaries of the predictive dose-response profiles for both Westerners and Asians.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, the final model, a simple E max model with a fixed E 0 (-0.812%), was successfully used to describe rosuvastatin pharmacodynamics. Moreover, the robustness of the final model was evaluated by the nonparametric bootstrap and the datasplitting methods [51,52] , which indicated that selected combinations of data yielded results very similar to those obtained using the original full data set. The predictive performance of the final model was confirmed by the visual predictive check using Monte Carlo simulations, which showed that the mean values of LDL-C reduction (%) from the one-dose trials were mostly distributed within the 5th-to 95th-percentile boundaries of the predictive dose-response profiles for both Westerners and Asians.…”
Section: Discussionmentioning
confidence: 94%
“…In order to compare intersubject variability, PK parameters of S-carvedilol were estimated by means of a two-compartment model with first-order absorption and elimination. The main finding of the study was the detection of a lower intersubject variability in the rate of S-carvedilol oral absorption for the CR formulation with regards to the IR dosage form [38].…”
Section: Population Pks Of B-blockersmentioning
confidence: 88%
“…In this context, a single population PK model has been developed to describe S-carvedilol PK from the immediate release (IR) and the CR dosage forms of the racemate [38]. In order to compare intersubject variability, PK parameters of S-carvedilol were estimated by means of a two-compartment model with first-order absorption and elimination.…”
Section: Population Pks Of B-blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference contributes, in part, to slightly higher milligram dosage strengths of carvedilol CR than the "equivalent" carvedilol IR doses . A model of carvedilol pharmacokinetics that takes into consideration both the IR and CR formulations has been developed and performed robustly in leverage analyses (Othman et al 2007). Similar to carvedilol IR, the bioavailability and pharmacokinetics of carvedilol CR are infl uenced by food, and both formulations are recommended to be taken with food .…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%